2016
DOI: 10.1016/j.cellimm.2015.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance and immune suppression in the tumor microenvironment

Abstract: The concept of immunological tolerance has guided and permeated much of modern immunology. Ray Owen’s ground-breaking observations in twin cattle provided the first mechanistic explanation for tolerance to self-molecules and established tolerance as a beneficial process that protects the host against autoreactivity. However, his studies also opened the door to understanding that tolerance may be detrimental, such as occurs when cancer cells induce tolerance/immune suppression resulting in inhibition of anti-tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 110 publications
2
21
0
Order By: Relevance
“…It has been reported that T lymphocytes and their associated cytokines are abnormal in patients with cancer and are significantly involved in tumor development and progression . In the present study, we found that levels of CD8 + T cells and Th1 cells in peripheral blood of patients with NSCLC were significantly decreased, whereas Treg were increased, which were consistent with the previous findings .…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that T lymphocytes and their associated cytokines are abnormal in patients with cancer and are significantly involved in tumor development and progression . In the present study, we found that levels of CD8 + T cells and Th1 cells in peripheral blood of patients with NSCLC were significantly decreased, whereas Treg were increased, which were consistent with the previous findings .…”
Section: Discussionsupporting
confidence: 92%
“…(B) J774M cells were treated with IFNg for 24 h and lysed for nuclear extract preparation. The nuclear extracts were incubated with that MDSCs massively accumulate in human cancers including colorectal cancer, [52][53][54] our findings thus raise the notion that in addition to the tumor cells, the PDL1 C MDSCs might be another major source of PD-L1 that inhibits tumor-infiltrating CTL activation and function in the tumor microenvironment. 17,55 The relative role of these PDL1 C MDSCs in colon cancer immune escape and resistance to immune checkpoint immunotherapy requires further studies.…”
Section: Discussionmentioning
confidence: 64%
“…Regulatory T-cells (Tregs) and tumor-associated macrophages (TAMs) comprise the majority of tumor-infiltrating cells associated with immune suppression in the tumor microenvironment [79]. The anti-inflammatory cytokines, interleukin-10 (IL-10), IL-4, and transforming growth factor- β 1 (TGF- β 1), mediate local immune suppression and promote increased infiltration of Tregs and TAMs.…”
Section: Introductionmentioning
confidence: 99%